Circulatory pulmonary artery denervation in patients with severe pulmonary hypertension undergoing combined mitral valve surgery and procedure Maze IV - Egorovich, Babokin Vadim; Alexandrovich, Trofimov Nikolai; Pavlovich, Medvedev Aleksander; Viktorovich, Nikolskiy Alexander; Gennadievich, Dragunov Andrey; Vadimovna, Babokina Sofia (Journal of Cardiovascular Medicine and Cardiology, 2020)
Background: The aim of this study was to evaluate the impact of sympathetic denervation of the pulmonary trunk and main pulmonary arteries on outcomes of surgical treatment in patients with mitral valve dysfunction, complicated by atrial fibrillation (AF) and severe Pulmonary Hypertension (PH). Method: Between September 2013 and July 2019, 140 patients with mitral valve dysfunction, concomitant AF and severe PH (mean pulmonary arterial pressure, MPAP, greater than 40 mmHg) who underwent cardiac surgery were analyzed. In the Denervation group, 51 patients underwent mitral valve surgery, biatrial Maze IV procedure and radiofrequency denervation of trunk and both main pulmonary arteries (pulmonary artery denervation, PADN). In the control group, 89 patients underwent the same surgery stages without PADN procedure. Results: Circular pulmonary artery denervation (PADN) contributes to a significant reduction in secondary PH (p = 0.018), reverse remodeling of the heart chambers, in particular the left atrium (p = 0.01), is an effective and safe method, and improves the results of the Maze IV procedure (p = 0.022) due to the sinus rhythm restoration, in patients with mitral valve dysfunction, complicated by AF and PH. Conclusions: Circulatory PADN additional to mitral valve surgery and Maze procedure represents a safe and effective treatment method for patients with mitral valve dysfunction, complicated by AF and severe PH. It is necessary to continue the study of this technique involving a larger number of patients, to analyze long-term outcomes and use this technique in patients with non-valvular causes of secondary PH.